Identification of candidate gene for the defective kernel phenotype using bulked segregant RNA and exome capture sequencing methods in wheat - Tang, Hao; Dong, Huixue; Guo, Xiaojiang; Cheng, Mengping; Li, Maolian; Chen, Qian; Yuan, Zhongwei; Pu, Zhien; Wang, Jirui (Frontiers in Plant Science, 2023)
Wheat is a significant source of protein and starch worldwide. The defective kernel (Dek) mutant AK-3537, displaying a large hollow area in the endosperm and shrunken grain, was obtained through Ethyl methane sulphonate (EMS) treatment of the wheat cultivar Aikang 58 (AK58). The mode of inheritance of the AK-3537 grain Dek phenotype was determined to be recessive with a specific statistical significance level. We used bulked segregant RNA-seq (BSR-seq), BSA-based exome capture sequencing (BSE-Seq), and the ΔSNP-index algorithm to identify candidate regions for the grain Dek phenotype. Two major candidate regions, DCR1 (Dek candidate region 1) and DCR2, were identified on chromosome 7A between 279.98 and 287.93 Mb and 565.34 and 568.59 Mb, respectively. Based on transcriptome analysis and previous reports, we designed KASP genotyping assays based on SNP variations in the candidate regions and speculated that the candidate gene is TraesCS7A03G0625900 (HMGS-7A), which encodes a 3-hydroxy-3-methylglutaryl-CoA synthase. One SNP variation located at position 1049 in the coding sequence (G>A) causes an amino acid change from Gly to Asp. The research suggests that functional changes in HMGS-7A may affect the expression of key enzyme genes involved in wheat starch syntheses, such as GBSSII and SSIIIa.